Improvement of Storability of BaftaimOnion (Allium cepa L.) Cultivar by Crossing with Abufrewa - Elkashif, Mohamed Elhag; Ismail, Fathia E.; Eljack, Ali E. (Gezira Journal of Agricultural Science; Vol 18 No 2 (2020), 2021)
Onion is one of the most important horticultural crops in the Sudan with regard to production and consumption. It has played an important role in human nutrition and medicine. The objective of this research was to determine the storability of some onion genotypes under direct sunshine, shade or refrigerated storage conditions. This research was conducted at the Faculty of Agricultural Sciences, University of Gezira, Wadmedani, Sudan during the seasons of 2014to 2017.Crosses were made between Baftaim and Abufrewa and F 1 was  produced. Then, F 1 was selfed to produce F 2 in the second season. Intensive selection was practiced for the desirable traits of parent Abufrewa and for the general features of parent Baftaim. Also, the F 1   ( Baftaim x Abufrewa ) was backcrossed to Baftaim to obtain BC 1 .  Then, the F 1 ( Baftaim x Abufrewa ) was backcrossed to  Abufrewa to obtain BC 2 . Genotypes consisted of two parents and four crosses. Samples of 5 kg of bulbs were taken randomly from each genotype and packed in jute bags. Onion bulbs from the genotypes were stored under three types of storage methods, namely, traditional storage under sun shine ( control), shade storage and refrigerated storage (0- 2.5ºC and  70-75% RH). A split-plot design with storage methods as the main plots and genotypes as the sub- plots was used and replicated two times for each method for six genotypes, namely, Baftaim,Abufrewa , F 1 , F 2 , BC 1 and BC 2 . The experiment was terminated after five months of storage from June to October for two seasons. Data were taken on total losses which consisted of weight loss (%), rotted bulbs (%), sprouted bulbs (%) and green bulbs (%).Results indicated highly significant differences among storage methods on total losses (%) in both seasons. The lowest losses percentages were recorded in the refrigerated method, followed by the shade method and the highest losses were recorded in the traditional method in both seasons. Results also indicated highly significant differences among onion genotypes on total losses (%) in both seasons. The least losses were recorded for Abufrewa followed by F 2, BC 2, F 1 and then BC 1, while the highest losses were recorded for Baftaim in both seasons. In conclusion, it is recommended to continue backcrossing with Abufrewa cultivar to produce genotypes with good storability and use refrigerated storage to reduce post-harvest losses in onion.